UMP Career and Entrepreneurship Carnival offers more than 1,000 internship and job opportunities - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PAYA BESAR, 11 June 2023 - More than 1,000 job and training opportunities were offered through the UMP Career and Entrepreneurship Carnival held for two days at the Astaka Hall, UMP Gambang Campus recently.